Analisis Faktor Ketertarikan Minuman Kopi Kekinian Terhadap Minat Beli Konsumen di Cirebon - Ratna Puspita Dewi; Sudiana Wachyudi (Politeknik Kampar, 2024)
The growing popularity of contemporary beverages, especially coffee drinks, among young people has resulted in increased competition among beverage establishments. This is evident from the emergence of numerous coffee shops offering unique and thematic experiences. As a result, the author is conducting research to explore the factors that attract young consumers to contemporary coffee drinks and how these factors influence their purchasing decisions. The study utilizes qualitative and quantitative descriptive methods and employs purposive sampling to select respondents from the young adult population in Cirebon who have an affinity for coffee drinks. The findings from interviews and field observations have revealed several key factors that contribute to the appeal of contemporary coffee drinks among young consumers. These include the ambiance of the coffee shops, the friendly and attentive service, the wide variety of delicious flavors and offerings, as well as the allure of distinctive shop and menu names. Additionally, the affordability of the products, coupled with creatively designed and eye-catching packaging, also significantly influences consumer interest. Furthermore, the study indicates that personal, social, and psychological factors play a role in driving the interest in purchasing contemporary coffee drinks among young people. It is hoped that this research will provide valuable insights for entrepreneurs in the coffee beverage industry and will serve as a basis for further exploration in this area.